Newborn care practices in rural Bangladesh - Islam MT; Islam N; Yoshimura Y; Nisha MK; Yasmin N (Dove Medical Press, 2015)
Mohammad Tajul Islam,1 Nazrul Islam,2 Yukie Yoshimura,1 Monjura Khatun Nisha,3 Nawzia Yasmin4 1Safe Motherhood Promotion Project, Japan International Cooperation Agency (JICA), Dhaka, Bangladesh; 2School of Population and Public Health, Faculty of Medicine, University of British Columbia, Vancouver, BC, Canada; 3International Centre for Diarrhoeal Disease Research, Bangladesh (icddr,b); 4Department of Public Health, State University of Bangladesh, Dhaka, Bangladesh Background: Neonatal mortality is high in Bangladesh. Most of the neonatal deaths are preventable through simple and cost-effective essential newborn care interventions. Studies to document the determinants of unhealthy newborn care practices are scarce. Objective: The objective of this study is to describe the pattern of neonatal care practices and their determinants in rural Bangladesh. Methodology: This study is based on baseline data of a community-based intervention to assess impact of limited postnatal care services on maternal and neonatal health-seeking behavior. Data from 510 women, who had a live birth at home 1 year prior to survey, of six randomly selected unions of an Upazila (subdistrict) were analyzed. Results: Majority of the respondents were at an age group of 20–34 years. Only 6% had delivery by skilled providers. Immediate drying and wrapping, and giving colostrums to newborns were almost universal. Unhealthy practices, like unclean cord care (42%), delayed initiation of breastfeeding (60%), use of prelacteals (36%), and early bathing (71%) were very common. Muslims were more likely to give early bath (adjusted odds ratio [OR]: 2.01; 95% confidence interval [CI]: 1.13–3.59; P=0.018) and delay in initiating breastfeeding (adjusted OR: 1.45; 95% CI: 1.18–1.78; P<0.001) to newborns. Practice of giving prelacteals was associated with teenage mothers (adjusted OR: 2.26; 95% CI: 1.19–4.28; P=0.013) and women’s lack of education (adjusted OR: 2.64; 95% CI: 1.46–4.77; P=0.001). Conclusion: Unhealthy neonatal care practices are widespread in rural Bangladesh. Continued education to the community and home delivery attendants on essential newborn care could benefit newborn survival in Bangladesh. Keywords: newborn care, cord care, bathing, breastfeeding, prelacteals, determinants, Bangladesh